The larva of Phyllogomphoides pugnifer Donnelly, 1979 (Odonata: Gomphidae) - Novelo-Gutiérrez, Rodolfo; Gómez-Anaya, José Antonio (Zootaxa, 2019)
The larva of Phyllogomphoides pugnifer Donnelly, 1979 is described for the first time based on reared specimens to emergence, and several F-0 larvae collected in Chiapas and Veracruz states, Mexico. The larva of P. pugnifer can be separated from other larvae of the genus by the length/width proportion of structures such as prementum, ligula, and abdominal segment 10, as well as length of cercus relative to epiproct.